Information Use Pattern of Faculty Members in Madurai Kamaraj University, Madurai - Balasubramanian, P.; Baladhandayutham, A. (Journal of Information and Knowledge, 2008)
This article discusses the results of a study of the information use pattern of faculty members of Madurai Kamaraj University in Madurai. Data were collected from seven schools in Maduai Kamaraj University. Results show that one hundred and thirty five respondents (45 percent) seek information for preparing lectures. Forty four percent of faculty members access more information from Internet. Seventy six percent of respondents read information materials in English and twenty percent read materials in Tamil. Most of the respondents used Google.com for searching information. They use frequently e-mail for communication. It is found that 25 percent of respondents use the Biotech database. Majority of respondents faced the common problem while seeking information i.e. lack of time and unavailability of information.